2010
DOI: 10.1186/1476-511x-9-68
|View full text |Cite
|
Sign up to set email alerts
|

Soybean and fish oil mixture increases IL-10, protects against DNA damage and decreases colonic inflammation in rats with dextran sulfate sodium (DSS) colitis

Abstract: It was investigated whether dietary polyunsaturated fatty acids (PUFA) could influence colonic injury, tissue DNA damage, cytokines and myeloperoxidase activity (MPO) and plasma corticosterone in DSS-induced colitis rats. Male weaning Wistar rats were fed for 47 days with an AIN-93 diet with control (C), fish (F) or a mixture of fish and soybean oil (SF). The colitis was induced from day 36 until day 42 by 3% DSS in drinking water. On day 48, blood samples were collected for corticosterone determination. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…We used custom-prepared diets to show that, in the postweaning animal, colonic membrane phospholipids are remarkably plastic to substantial alteration in their n-6 and n-3 fatty acids within a relatively short 4-wk period of altering the fatty acid but not fat content of the diet. High intake of 20:5n-3 and 22:6n-3 consumed before and during the course of C. rodentium infection attenuated colonic injury, consistent with the beneficial effect of dietary n-3 fatty acids observed in other experimental models of colitis (1,4,11,42). In contrast, high n-6 fatty acid intake exacerbated the inflammatory response.…”
Section: Discussionsupporting
confidence: 77%
“…We used custom-prepared diets to show that, in the postweaning animal, colonic membrane phospholipids are remarkably plastic to substantial alteration in their n-6 and n-3 fatty acids within a relatively short 4-wk period of altering the fatty acid but not fat content of the diet. High intake of 20:5n-3 and 22:6n-3 consumed before and during the course of C. rodentium infection attenuated colonic injury, consistent with the beneficial effect of dietary n-3 fatty acids observed in other experimental models of colitis (1,4,11,42). In contrast, high n-6 fatty acid intake exacerbated the inflammatory response.…”
Section: Discussionsupporting
confidence: 77%
“…Although tissue and dietary ratios are difficult to compare, it is possible that a very high dose of fish oil is detrimental in colitis, whereas a moderate dose is protective. In the present study, we used a much higher dose of fish oil (27.2% kcal) compared with all previous studies on fish oil and colitis (17.2% kcal) (33,(36)(37)(38). However, because we did not see any significant effect from fish oil, this difference does not explain discrepancies among previous studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Whereas some studies have shown that fish oil supplementation (5% wt:wt) reduces DSS-induced weight loss and DNA damage (33) or that other n-3 (v) oils ameliorate inflammation in the same model (34,35), several studies report the opposite. Fish oil, varying between 0.75 and 8% wt:wt, has severely exacerbated colitis scores in several colitis models: DSS colitis (36), the IL-10 knockout mouse (37), and the H. hepaticus-induced colitis model (38), in which fish oil resulted in a dose-dependently higher intestinal histopathological score.…”
Section: Discussionmentioning
confidence: 97%
“…Diet with 6% fish oil and 1% corn oil (n-6:n-3 ratio of 0.17) aggravated the colitis [36]. Another study demonstrated that compared to fish oil alone, fish oil and soybean oil blend (n-6:n-3 ratio of 2) attenuate DSS induced colitis [37]. These studies suggest that high dosage of fish oil is detrimental to the colitis whereas moderate dose is protective.…”
Section: Discussionmentioning
confidence: 92%